Analisis Preferensi Mahasiswa pada Mata Kuliah Peminatan dengan Metode Statistik Deskriptif - Mahesa, Ilham; Antika, Cinta Dewi; Sari, Maida Yusna; Pradifta, Bagas; Nasution, Adelyna Oktavia (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to analyze the interests of Information Systems students in elective courses offered by the program. The objective of this research is to determine the extent to which students tend to choose courses based on their interests and the relevance of those courses to their future careers. The research is categorized as quantitative, using a non-experimental approach and descriptive method. The data used in this study are quantitative in nature, consisting of numerical values obtained from 50 students who voluntarily expressed their preferences for three elective courses: Data Mining, Machine Learning, and Interactive Educational Applications. After the data were collected, they were processed using percentage analysis to determine the distribution of student interest in each course. The results were then presented in the form of diagrams to provide a clearer visual representation. Based on the research findings, the results show that: 1) The Data Mining course ranked first with the highest level of interest, at 66%. Most students chose this course because it is considered more beneficial for future careers and easier to understand. 2) In second place was the Machine Learning course, with an interest level of 18%, where students were drawn to the subject due to its alignment with their personal interests. 3) Finally, Interactive Educational Applications ranked third with 16%, with most students selecting it based on recommendations from their Academic Advisors.